Methods of testing refractory materials. Properties measured under an applied stress. Determination of resistance to abrasion at elevated temperature up to 1400°C (abradability index at elevated temperatures) (method 1902-407) Part 4-4.7, (28th February 1985) - British Standards Institution,
No abstract available